Universal characteristics of magnetic losses in electric traction machines - Afanasov, O. M. (Science and Transport Progress, 2013)
The analysis of dependence of the magnetic losses in hauling electric motors on the frequency of armature remagnetization is presented. A universal characteristics of the magnetic losses reduced to the frequency of remagnetization of 50 Hertz is offered.